Faktor-Faktor yang Mempengaruhi Senjangan Anggaran - Anik Irawati; Anisa Mutiara (Politeknik Negeri Lampung, 2018)
This study was aimed at demonstrating the influence of budget participation as an independent variable, the asymmetry of information, the capacity of individuals and organizational commitment as moderating variables on the incidence of budgetary slack as the dependent variable. The sampling method in this study was purposive sampling, namely the regional device organization (OPD) at Bandar Lampung in the form of the department, in order to obtain 16 Departments with a number of respondents as many as 74 people. The data were collected through survey in the form of a questionnaire and analyzed using moderated regression analysis. The study results show that budget participation influenced the budgetary slack, as well as the organizational commitment influenced the relationship between budgetary participation and budgetary slack. Meanwhile, the asymmetry of information and the capacity of individuals did not influence the relationship between budgetary participation and budgetary slack.